Low cost carriers and tourism in ASEAN - Chua, Bao Zeng (2009)
The rise of low cost carriers (LCCs) in the ASEAN (Association of Southeast Asia Nations) region has led to a new phase of development in the region’s aviation and tourism industry. This paper aims to examine the possibility of LCCs as a driver to ASEAN’s tourism and what impacts they may bring to the region’s tourism. Attention is also given to both the various government initiatives in creating a LCC friendly environment and the future outlook of its LCC industry. The paper concludes with the importance of the tri-lateral relationship amongst LCCs, the Southeast Asian government and the tourism industry.